Yoga Dalam Mengatasi Gejala Psikosomatis Mahasiswa di Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja - Murniti, Ni Wayan; Marselinawati, Putu Sri (Jurnal Penelitian Agama Hindu, 2023)
The busy activities of students both in participating in activities on campus and outside the campus result in fatigue and trigger the emergence of stress. Prolonged stress can disrupt health and cause physical illness (psychosomatic). Psychosomatics is a physical illness triggered by a pile of negative emotions. Psychosomatics can affect everyone without exception students. Someone who cannot direct their thoughts and feelings properly is vulnerable to psychosomatics. The cause of psychosomatics is negative emotions such as anxiety, anger, resentment, and sadness. Psychosomatic symptoms experienced by STAHN Mpu Kuturan Singaraja students are sleeplessness, indigestion, and respiratory problems. These psychosomatic symptoms can be synergised with yoga activities. The purpose of this study was to determine the benefits and contribution of yoga in overcoming psychosomatic symptoms in students at STAHN Mpu Kuturan Singaraja. This type of research is qualitative research, primary data obtained from interviews with informants. Data collection was done by observation, literature study, and documentation. The data obtained was then analysed using qualitative descriptive techniques.  From the results of the study, it can be concluded that the practice of yoga carried out by UKM Yoga STAHN Mpu Kuturan Singaraja is beneficial and contributes to overcoming psychosomatics.